Age related changes seen in human cornea in formalin fixed sections and on biomicroscopy in living subjects: A comparison - Taurone, Samanta; Miglietta, Selenia; Spoletini, Marialuisa; Feher, Janos; Artico, Marco; Papa, Veronica; Matassa, Roberto; Familiari, Giuseppe; Gobbi, Pietro; Micera, Alessandra (Clinical anatomy (New York, N.Y.), 2020)
The purpose of our experimental research was to assess the effects of aging on the main corneal structures in healthy corneas. Small, human cornea samples were collected from 20 Caucasian subjects during surgery for traumatic lesions to the eye. Ten subjects were adults (mean age 28 years) and 10 were elderly (mean age 76 years). Morphological analysis was carried out using light microscopy and electron microscopy. Another 40 patients (20 young: mean age < 30 years; 20 elderly: mean age > 70 years) were studied in vivo by confocal microscopy. The resulting images were analyzed qualitatively, quantitatively, and statistically. The basic light microscope revealed a decrease in endothelial cell density with age accompanied by an increase in endothelial cell size. Transmission electron microscopy revealed a corneal thinning and a decrease in the number of corneal stromal cells. A marked decrease in stromal nerve fibers was observed in the older subjects compared to the younger ones. Variable pressure scanning electron microscopy (VP‐SEM) was used to make surface morphological observations and to determine the chemical composition of in vivo hydrated human corneas. Our results showed the effects of aging on normal corneal morphology highlighting the structural diversity of the corneal layers and revealing an age‐related reduction in nerve fibers, thus explaining the decreased corneal sensitivity that may be observed in the elderly. Clin. Anat. 33:245–256, 2020. © 2019 Wiley Periodicals, Inc.